The effect of exercises with oxygen lacking masks on the speed storage and the achievement of 800m runners under 18 years old - Khudhair, Husham Hasan; Majhool, Zuhair Salih; JAWAD, ALAA FLAYYlH (International Journal of Psychosocial Rehabilitation, 2020)
Athletics is one of the sports task that you need all fitness components of fitness , in order to upgrade these components can develop the physical aspects through which they can develop the sporting achievement , because all the effectiveness of these activities require special specifications of the different each one from the other in all its components and i saliva performance And its technical stages. The effectiveness ran 800 m enemy competitions distances medium fast exciting Olympic and globally in athletics , which features a range of features and qualities of its own a where you need to your endurance , and this on the coach to choose F should err training methods and the most influence on these variables to reach the best achievement for this event , and these modern methods exercises (masks a lack of oxygen ) , which is one of the exercises significant lack of oxygen and have positive effects in the special abilities that depend on the completion of the effectiveness of 80 0 m .